(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents the theoretical and methodological foundations of a study on the documentation of stage lighting as an expression of technical-artistic knowledge. It proposes an archival-artistic approach based on interviews and the collection of documents from professionals in Brazil, Argentina, and Italy. Operational concepts, criteria for the study of document typologies, and methodological procedures are outlined, along with initial reflections on the meanings attributed to these materials. The proposal contributes to recognising these documents as part of the history of performance.